The association of climate-induced stressors on risk of negative sentiment: an analysis from 462 million geotagged tweets in Europe - Al-Ahdal, Tareq; Barman, Sandra; Alahmad, Barrak; Dafka, Stella; Gallo, Elisa; Ballester, Joan; Sofiev, Mikhail; Romanello, Marina; Bärnighausen, Till; Gertz, Michael; Rocklöv, Joacim (iScience, 2025)
This study examines how climate-induced health risks influence negative sentiments on European social tweets from 2015 to 2022. Analyzing over 400 million tweets using NLP tools (NLTK, LIWC22) and spatial-temporal aggregation at the NUTS2 weekly level, we applied a Poisson generalized additive model (GAM) with integrated nested Laplace approximation (INLA) and fused lasso regularization to capture sentiment fluctuations. Results show negative sentiments rise by up to 0.36% when maximum temperatures exceed 26.9°C and by 0.49% during severe droughts (SPI < −3.72). Elevated alder pollen counts (>135 grains/m3) also increase risk of negative sentiment by 0.21%, while temperatures below 2.9°C reduce it by 0.63%. No significant association was found with heat-related mortality or West Nile virus incidence. These findings suggest specific climate-related health factors - high temperatures, droughts, and pollen - trigger negative social media reactions, whereas others, such as mortality and infectious outbreaks, appear unnoticed in public sentiment.
Online verfügbar: 3. November 2025, Artikelversion: 18. November 2025
Gesehen am 28.01.2026